2019
DOI: 10.1038/s41550-019-0801-4
|View full text |Cite
|
Sign up to set email alerts
|

Migration of D-type asteroids from the outer Solar System inferred from carbonate in meteorites

Abstract: Recent dynamical models of Solar System evolution and isotope studies of rock-forming elements in meteorites have suggested that volatile-rich asteroids formed in the outer Solar System beyond Jupiter's orbit, despite being currently located in the main asteroid belt 1-4 . The ambient temperature under which asteroids formed is a crucial diagnostic to pinpoint the original location of asteroids and is potentially determined by the abundance of volatiles they contain. In particular, abundances and 13 C/ 12 C ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 58 publications
3
62
0
Order By: Relevance
“…Constrained MHD models of our nebula argue that the magnetic field it supported reached this intensity at a heliocentric distance of ∼9.8 AU, indicating that the WIS 91600 parent body formed in the far reaches of the solar system. As such, our results support previous claims (Bryson et al 2020;Fujiya et al 2019) that the parent asteroids of some meteorites formed in this region of the solar system.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Constrained MHD models of our nebula argue that the magnetic field it supported reached this intensity at a heliocentric distance of ∼9.8 AU, indicating that the WIS 91600 parent body formed in the far reaches of the solar system. As such, our results support previous claims (Bryson et al 2020;Fujiya et al 2019) that the parent asteroids of some meteorites formed in this region of the solar system.…”
Section: Discussionsupporting
confidence: 92%
“…As such, the paleointensities recovered from bulk meteorites and their components that recorded magnetic remanences within the lifetime of the solar nebula can be used as a proxy for the formation distances of their parent asteroids within the solar system. This approach has been applied to the ungrouped C2 chondrite Tagish Lake, a unique meteorite with mineralogical and chemical signatures (Brown et al 2000;Hiroi et al 2001;Zolensky et al 2002;Grady et al 2002;Fujiya et al 2019) that suggest its parent body formed at a larger heliocentric distance than those of most other meteorites (i.e., 4 AU, Desch et al 2018). Tagish Lake was extensively aqueously altered on its parent asteroid (Zolensky et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, alteration on Ceres may have involved systems richer in volatile species (H, C, N) than is typical for CCs, possibly due to accretion of materials located outside NH 3 snowline (De Sanctis et al, 2015) and/or ice-rock differentiation (Ermakov et al, 2017;Park et al, 2016). Such a distant origin has been discussed for Tagish Lake parent body from the high abundance of 13 C-rich carbonates (Fujiya et al, 2019). Our model showed that Ceres can be modeled by mixing of Tagish Lake-like materials with amorphous carbon, IOM, and other hydrous minerals (B3, Figure 12).…”
Section: Implications For Formation and Evolution Of Ceresmentioning
confidence: 99%
“…These two extreme cases for the captured model may be tested on the basis of the heliocentric gradients of volatile isotopes and abundances (e.g., CO 2 /H 2 O, D/H, 15 N/ 14 N and noble gases) and the isotopes of rock-forming elements of O, Cr, and Ti in the solar system (Figs. 2, 3, and 4) (Trinquier et al 2007;Trinquier et al 2009;Qin et al 2010;Warren 2011;Marty 2012;Fujiya et al 2019).…”
Section: A Case Of the Captured Asteroid Hypothesismentioning
confidence: 99%
“…The CO 2 /H 2 O ratios of ice in CM chondrites are calculated from carbonate abundances and hydrogen contents. Modified afterFujiya et al (2019)…”
mentioning
confidence: 99%